Shear Wave Elastographic Alterations in the Kidney After Extracorporeal Shock Wave Lithotripsy. (13th October 2017) - Turkay, Rustu; Inci, Ercan; Bas, Derya; Atar, Arda
Abstract : Objectives: Extracorporeal shock wave lithotripsy (ESWL) is a method used frequently for the treatment of renal stone disease. Although its safety is proven, there are still concerns about its unwanted effects on kidneys. In this prospective study, we aimed to evaluate renal tissue alterations with shear wave elastography (SWE) after ESWL. We also studied the correlation between SWE and resistive index (RI) changes. Methods: The study included 59 patients who underwent ESWL treatment for renal stone disease. We performed SWE and color Doppler ultrasonography to calculate SWE and RI values before, 1 hour after, and 1 week after lithotripsy treatment. A binary comparison was performed by the Bonferroni test. The correlation between SWE and RI values was evaluated by a Pearson correlation analysis. Results: The patients included 26 women (44.1%) and 33 men (55.9%). Their ages ranged from 20 to 65 years (mean ± SD, 45.0 ± 1.1 years). Stone diameters ranged from 7 to 19 mm (mean, 13.0 ± 0.5 mm). There was a significant difference in SWE values before and 1 hour after lithotripsy treatment ( P  = .001; P  < .01). In the follow‐up measurement 1 week after treatment, this difference disappeared ( P  > .99; P  > .05). Resistive index values increased significantly 1 hour after lithotripsy treatment and returned to prelithotripsy values 1 week after treatment. In the correlation analysis, SWE and RI values were not correlated. Conclusions: Measurements of alterations in SWE values after ESWL can provide useful information about renal tissue injury.